ENTERPRISE ARCHITECTURE DESIGN ON IMPROVING DISKOMINFO SERVICES IN CENTRAL LOMBOK REGENCY USING TOGAF 9.2 - Baiq Vidisasca Suhita; Asti Amalia Nur Fajrillah; Widyatasya Agustika Nurtrisha (STMIK Royal, 2023)
Abstract: Currently, the increasing needs of the community to obtain efficient, effective, transparent and accountable public services. Various applications are designed in order to realize a transparent work system of accountable funds and an increase in work processes that are fast, precise, and accurate. Therefore, local governments are now developing e-Government or in the Indonesian government known as the Electronic-Based Government System (SPBE). In running SPBE, the Central Lombok Regency Government, especially the Department of Communication and Informatics, participates in developing SPBE, one of which is in the Informatics Application Division which has an Informatics Application Management Program. This research aims to support SPBE-based informatics application management services for OPDs in Central Lombok Regency and the public. This SPBE design adopts the TOGAF 9.2 approach, and is also adjusted to the Presidential Regulation on Electronic-Based Government Systems in designing. This research focuses on the Informatics Application Management Program with business process architecture domain, service architecture domain, data and information architecture domain, application architecture domain, and technology (infrastructure) architecture domain. The result of this research is a blueprint that will be used as a solution or support for the running of SPBE in the Informatics Application Management Program. Keywords: electronic-based government system, department of communication and informatics, informatics application management program, togaf 9.2 Abstrak Saat ini, meningkatnya kebutuhan masyarakat untuk mendapatkan pelayanan publik yang efisien, efektif, transparan dan akuntabel publik. Berbagai aplikasi di rancang agar dapat mewujudkan sistem kerja yang transparan dana akuntabel serta adanya peningkatan proses kerja yang cepat, tepat, dan akurat. Maka dari itu, Pemerintah daerah kini mengembangkan e-Government atau di pemerintahan Indonesia dikenal sebagai Sistem Pemerintahan Berbasis Elektronik (SPBE). Dalam menjalankan SPBE Pemerintah Kabupaten Lombok Tengah khususnya Dinas Komunikasi dan Informatika ikut serta mengembangkan SPBE salah satunya pada Bidang Aplikasi Informatika yang memiliki Program Pengelolaan Aplikasi Informatika. Dalam penelitian ini memiliki tujuan untuk menunjang layanan pengelolaan aplikasi informatika berbasis SPBE bagi OPD yang ada di Kab. Lombok Tengah dan juga publik. Perancangan SPBE ini mengadopsi pendekatan TOGAF 9.2, dan juga di sesuaikan dengan Peraturan Presiden tentang Sistem Pemerintahan Berbasis Elektronik dalam melakukan perancangan. Penelitian ini berfokus pada Program Pengelolaan Aplikasi Informatika dengan domain arsitektur proses bisnis, domain arsitektur layanan, domain arsitektur data dan informasi, domain arsitektur ap-likasi, dan domain arsitektur teknologi (infrastruktur). Hasil dari penelitian ini yaitu suatu blueprint yang nantinya akan dijadikan solusi ataupun penunjang berjalannya SPBE dalam Program Pengelolaan Aplikasi Informatika. Kata kunci: aplikasi informatika, program pengelolaan aplikasi informatika, enterprise architecture, togaf 9.2